A Survey on E-Commerce Support Using Chatbot - Singh Kushwah, Neeraj; Ayush; J. , Prathipa (International Journal of Psychosocial Rehabilitation, 2020)
The issue of consumer loyalty and experience is extremely central in any Business, for example, ECommerce Industry. E-commerce provides a unique way which allows business globally. In well-developed economic countries, the consumer pattern has also changed because of the E-Commerce industries. E- commerce requires the interaction of both customer and retailer for a successful business. This paper provides information about various e-commerce Chatbot and techniques which simplify interaction between customers and seller. Chatbot enables the client to determine their inquiry with no additional exertion and presents another path for the client to collaborate with the framework. A Chatbot helps the user in a way such that it can ask their queries as they would ask a normal agent. A Chatbot provides a medium through which customer can ask queries and commercial Industry can answer all queries and can provide support by using Chatbot services. This will help us in reducing the time for customer support and helps to enhance business profit. Machine Learning, Natural Language Processing and Deep learning techniques are used to build Chatbot. Analysis of several Chatbot and techniques is presented in a comprehensive manner.